PUBLIC FOOD POLICIES: THE CONTRIBUTION OF GOVERNMENT PROCUREMENT TO THE PRODUCTIVE INCLUSION OF FAMILY FARMERS IN THE STATE OF TOCANTINS - Sousa, Diego Neves de; Beraldo, Keile Aparecida (Revista Brasileira de Gestão e Desenvolvimento Regional, 2023)
The aim of this study was to analyze the contribution of Government Procurement to the productive inclusion of family farmers in the context of the state of Tocantins. With a quantitative and qualitative research approach, 80 mediators, who work with family farming audiences, were interviewed. The results point to the potential of Government Procurement for the productive inclusion of family farmers. The explanation is that they are linked to the positive effects of encouraging collective and formal organization of family farmers, increasing family income, boosting the local economy, valuing regional products, ensuring insertion in new markets and contributing to food security for direct and indirect beneficiaries. On the other hand, the bureaucracy and low organization of farmers are the main variables responsible for the difficulties in implementing public food policies.